Learning Leadership from Dogs : What Can Bulldogs, Dachshunds, Komondors, Pekingese and Otterhounds (among Other Dogs) Teach Us about Effective Leadership?. - Simha, Aditya (Anthem Press, 2025)
The book uses the context and world of dogs to aid the reader's understanding of leadership. The reader will learn about leadership concepts and also about several breeds of dogs, across the world, including breeds such as the Bulldog, Dachshund, German Shepherd, Mastiff and Otterhound, among others.
Description based upon print version of record.
Keywords: Leadership.; Dogs.; Dog breeds.; Chiens.; Chiens -- Races.; Management.; BUSINESS & ECONOMICS.; Breeds.; PETS.; Electronic books.